Novel environmental class 1 integrons and cassette arrays recovered from an on-farm bio-purification plant - Martini, María Carla (2018)
Rapid dissemination and emergence of novel antibiotic resistance genes among bacteria are rising problems worldwide. Since their discovery in clinical isolates in the late 1980s, class 1 integrons have been found in a wide range of bacterial genera and have been extensively studied as contributors to dissemination of antibiotic resistance. The present study aimed to investigate the presence and structure of class 1 integrons in plasmid-carrying bacterial isolates obtained from a biopurification system used for decontamination of pesticide-contaminated water as well as their possible role as reservoir of antimicrobial resistance gene cassettes. A total of 35 representative isolates were screened for the presence of class 1 integron integrase encoded by intI1. PCR and DNA sequencing revealed the presence of six class 1 integrons with four variable regions: 5΄CS-aadA1b-3΄CS, 5΄CS-aadA2-3΄CS, 5΄CS-aadA11cΔ-3΄CS and 5΄CS-dfrB3-aadA1di-catB2-aadA6k-3΄CS, the last two being unseen arrays of antimicrobial resistance gene cassettes associated with novel environmental alleles of intI1. These four class 1 integrons were identified as being present in four different genera, including Ochrobactrum, and Variovorax, where class 1 integrons have not been previously reported. The results provide evidence of the biopurification systems as a tank of class 1 integron carrying strains and novel environmental class 1 integron integrases associated with antimicrobial resistance gene cassette arrays.